Answer:
(x-3)(x-6)
Step-by-step explanation:
Fill in g into f and simplify:
(x-2)²-5(x-2)+4 =
x² - 4x + 4 - 5x + 10 + 4 =
x² - 9x + 18 =
(x-3)(x-6)
Not enough information to properly answer this... hope this helped though
The first step is to write this equation into general form. The
general form of an equation is:
ax^2 + bx + c = 0
To make this equation to general form, you have to simplify
the equation first.
2/3(x-4) (x+5) = 1
2/3 (x^2 + 5x – 4x – 20) = 1
2/3(x^2 + x -20) = 1
2/3x^2 + 2/3x – 40/3 = 1
2/3x^2 + 2/3x – 40/3 – 1 = 0
2/3x^2 +2/3x – 43/3 = 0
Therefore, a = 2/3 ; b = 2/3 ; c = -43/3
perimeter = Answer:
Step-by-step explanation:
5. Perimeter of semi circle = r(pi+2)
Given diameter=17m; r=17/2
Perimeter = (17/2)(pi+2)
6. Given diameter = 10.5
Perimeter = (10.5/2)(pi+2)